Agribusiness Development Strategy in Belitang Mulya District, East Oku District - Eko Suparyanto; Rini Efrianti; Yunita Sari (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to analyze the strategy for developing melon agribusiness in Belitang Mulya District, Kab. East OKU. The type of research used in this research is a quantitative descriptive method. The data analysis used in this research is SWOT analysis. Based on the results of the analysis of internal factors in melon farming, there are 4 strengths, namely supporting natural resources, including plants that are easy to care for, agribusiness actors have their own land. Has quite a long experience in the plant cultivation business, and has 4 weaknesses, namely. Melon productivity is still low. Melon processing is less than optimal, lack of attention from local government agencies, lack of knowledge of agribusiness actors in using digital markets. And external factors There are 3 opportunities (Opportunities), namely establishing relationships with stakeholders, post-harvest processed products. Increasing healthy lifestyles will increase demand for melons, and has 3 threats (Threats), namely the development of pests and diseases of melon plants, decreasing purchasing power due to the economic situation and damaged road infrastructure. Based on the results of the SWOT analysis of melon farming development strategies, there are strategies that can be applied to melon farming, namely maximizing land use, increasing cooperation with the government to obtain assistance in the form of materials and information, creating new processed products to increase selling value and attractiveness, and Minimize the development of melon pests and diseases in order to maximize melon productivity. And in the position matrix, melon farming is in position (1.55 :1.29) in quadrant I which shows that this melon farming is strong and has opportunities. The strategy given is aggressive, which uses strengths to achieve profitable opportunities. Keywords: Development strategy, melon, SWOT AbstrakPenelitian ini bertujuan untuk menganalisis strategi pengembangan agribisnis melon di Kecamatan Belitang Mulya Kab. OKU Timur. Jenis penelitian yang digunakan dalam penelitian ini adalah metode deskriptif kuantitatif. Analisis data yang digunakan dalam penelitian ini yakni analisis SWOT. Berdasarkan hasil anallisis faktor internal Usahatani melon terdapat 4 kekuatan (Strength) yaitu Sumber daya alam yang mendukung, Termasuk tanaman yang mudah dalam perawatannya, Pelaku Agribisnis memiliki lahan sendiri. Memiliki pengalaman yang sudah cukup lama dalam usaha budidaya tanaman, Dan mempunyai 4 kelemahan (Weakness) yaitu. Produktifitas melon masih rendah. Pengolaan melon kurang optimal, Kurangnya perhatian dari dinas pemerintahan setempat, Kurangnya pengetahuan Pelaku Agribisnis dalam menggunakan market digital. Dan faktor eksternal Terdapat 3 peluang (Opportunities) yaitu Terjalinnya hubungan dengan stakeholder, Produk olahan pasca panen. Peningkatan gaya hidup sehat sehingga mingkatkan permintaan melon, dan memiliki 3 ancaman (Threats) yaitu Perkembangan hama dan penyakit tanaman melon, Menurunnya daya beli karena situasi ekonomi dan Infrastruktur jalan yang rusak. Berdasarkan hasil dari analisis SWOT strategi pengembangan usahatani melon, memiliki strategi yang bisa di terapkan pada usahatani melon yaitu memaksimalkan penggunaan lahan, meningkatkan kerjasama dengan pemerintah untuk mendapatkan bantuan berupa material maupun pengetahuan informasi, menciptakan produk olahan baru untuk menambah nilai jual dan daya tarik, dan meminimalisirkan perkembangan hama dan penyakit melon agar dapat memaksimalkan produktivitas melon. Dan pada matriks posisi, usahatani melon berada pada posisi (1,55 :1,29) di kuadran I yang menunjukkan bahwa usahatani melon ini kuat dan berpeluang. Strategi yang diberikan adalah Agresif, diamana memanfaatkan kekuatan untuk meraih peluang yang menguntungkan.